Night-Warming Priming at the Vegetative Stage Alleviates Damage to the Flag Leaf Caused by Post-anthesis Warming in Winter Wheat (Triticum aestivum L.) - Fan, Yonghui; Lv, Zhaoyan; Ge, Ting; Li, Yuxing; Yang, Wei; Zhang, Wenjing; Ma, Shangyu; Dai, Tingbo; Huang, Zhenglai (Frontiers in Plant Science, 2021)
The asymmetric warming in diurnal and seasonal temperature patterns plays an important role in crop distribution and productivity. Asymmetric warming during the early growth periods of winter wheat profoundly affects vegetative growth and post-anthesis grain productivity. Field experiments were conducted on the wheat cultivars Yangmai 13 (YM13) and Yannong19 (YN19) to explore the impact of night warming treatment in winter (WT) or spring (ST) on the senescence of flag leaves and yield of wheat plants later treated with night warming during the grain filling period (FT). The results showed that FT decreased wheat yield by reducing the number of grains per panicle and 1000-grain weight and that the yield of wheat plants treated with FT declined to a greater extent than that of wheat plants treated with WT + FT or ST + FT. The net photosynthetic rate, chlorophyll content, and chlorophyll fluorescence parameters of flag leaves of wheat plants treated with WT + FT or ST + FT were higher than those under the control treatment from 0 to 7 days after anthesis (DAA) but were lower than those under the control treatment and higher than those of wheat plants treated with FT alone from 14 to 28 DAA. The soluble protein and Rubisco contents in the flag leaves of wheat plants treated with WT + FT or ST + FT were high in the early grain filling period and then gradually decreased to below those of the control treatment. These contents were greater in wheat plants treated with WT + FT than in wheat plants treated with ST + FT from 0 to 14 DAA, whereas the opposite was true from 21 to 28 DAA. WT + FT and ST + FT inhibited membrane lipid peroxidation by increasing superoxide dismutase and peroxidase activities and lowering phospholipase D, phosphatidic acid, lipoxygenase, and free fatty acid levels in the early grain filling period, but their inhibitory effects on membrane lipid peroxidation gradually weakened during the late grain filling period. Night-warming priming alleviated the adverse effect of post-anthesis warming on yield by delaying the post-anthesis senescence of flag leaves.